Pemanfaatan Pemasaran Melalui Media Sosial oleh UMKM Di Era Pandemi : Studi Kasus pada Usaha Mikro, Kecil, Dan Menengah di Kabupaten Bandung - Mira Veranita; Lukmanulhakim Almamalik; Sugiyanto Ikhsan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
The restrictions imposed to prevent the spread of the Corona virus have greatly impacted various types of businesses, both large-scale businesses and MSMEs and have indirectly forced business owners to make digital marketing, especially marketing through social media, one of the business solutions in marketing their business. This study aims to determine the use of social media as a marketing medium for MSMEs in the midst of various restrictions due to the Covid-19 pandemic. The method used in this study is a qualitative descriptive method. The subjects of this study were MSME actors under the guidance of the Cooperatives and SMEs Service, Bandung Regency, which were selected as many as 23 MSMEs using purvosive sampling technique. The research data was collected combining desk analysis and direct observation to MSME actors, interviews with key respondents from the Bandung Regency Cooperatives and SMEs Service, and digital marketing practitioners. The results of the study show that MSME actors have made social media a marketing method in this pandemic era. Marketing using social media is used because it is able to increase brand awareness, facilitate product feedback and marketing strategies, build networks with consumers, suppliers and competitors, but in a more convenient and cost effective manner.